2022
DOI: 10.1101/2022.06.17.496604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activity regulates a cell type-specific mitochondrial phenotype in zebrafish lateral line hair cells

Abstract: Hair cells of the inner ear are particularly sensitive to changes in mitochondria, the subcellular organelles necessary for energy production in all eukaryotic cells. There are over thirty mitochondrial deafness genes, and mitochondria are implicated in hair cell death following noise exposure, aminoglycoside antibiotic exposure, as well as in age-related hearing loss. However, little is known about the basic aspects of hair cell mitochondrial biology. Using hair cells from the zebrafish lateral line as a mode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In the zebrafish lateral line, the fusion/fission state is less clear in some published electron micrographs ( Dow et al, 2018 ;Laurà et al, 2018 ), with otherwise highly informative live imaging experiments lacking sufficient spatial resolution to provide further clarity on this specific issue ( Pickett et al, 2018 ). However, unpublished work specifically investigating mitochondrial morphology in the zebrafish lateral line HCs using SBF-SEM has revealed that apical mitochondria are smaller and more discrete, whilst those at the base of the cell form a larger reticular network ( McQuate et al, 2022 ). Disruption of network architecture results in a reduced mitochondrial response to mechanical stimulation of the HC.…”
Section: Mitochondrial Shapementioning
confidence: 99%
“…In the zebrafish lateral line, the fusion/fission state is less clear in some published electron micrographs ( Dow et al, 2018 ;Laurà et al, 2018 ), with otherwise highly informative live imaging experiments lacking sufficient spatial resolution to provide further clarity on this specific issue ( Pickett et al, 2018 ). However, unpublished work specifically investigating mitochondrial morphology in the zebrafish lateral line HCs using SBF-SEM has revealed that apical mitochondria are smaller and more discrete, whilst those at the base of the cell form a larger reticular network ( McQuate et al, 2022 ). Disruption of network architecture results in a reduced mitochondrial response to mechanical stimulation of the HC.…”
Section: Mitochondrial Shapementioning
confidence: 99%